Compatibilizing effects of maleic anhydride-grafted-polypropylene (PP)on long carbon fiber-reinforced PP composites. (November 2015) - Kim, JS; Kim, DH
We prepared long carbon fiber (LCF)-reinforced thermoplastic composites using a specially designed twin-screw system. To improve the interfacial adhesion strength between the matrix polypropylene (PP) and LCF, we used a compatibilizer (maleic anhydride-grafted PP (PPMA)). The fiber length of the composites was approximately 10–70 mm and influenced by the compatibilizer concentration. With an increase in the LCF and PPMA content, tensile strength, tensile modulus, flexural strength, and flexural modulus increase. We also investigated the thermal properties of the composites using thermogravimetric analysis and differential scanning calorimetry. The fractured surfaces of PP/PPMA/LCF composites exhibited higher wetting than those of PP/LCF composites. PPMA was found effective in improving the adhesion between fiber and matrix.